Hrs and SNX3 functions in sorting and membrane invagination within multivesicular bodies. - Véronique Pons (Public Library of Science (PLoS), 2008)
After internalization, ubiquitinated signaling receptors are delivered to early endosomes. There, they are sorted and incorporated into the intralumenal invaginations of nascent multivesicular bodies, which function as transport intermediates to late endosomes. Receptor sorting is achieved by Hrs--an adaptor--like protein that binds membrane PtdIns3P via a FYVE motif-and then by ESCRT complexes, which presumably also mediate the invagination process. Eventually, intralumenal vesicles are delivered to lysosomes, leading to the notion that EGF receptor sorting into multivesicular bodies mediates lysosomal targeting. Here, we report that Hrs is essential for lysosomal targeting but dispensable for multivesicular body biogenesis and transport to late endosomes. By contrast, we find that the PtdIns3P-binding protein SNX3 is required for multivesicular body formation, but not for EGF receptor degradation. PtdIns3P thus controls the complementary functions of Hrs and SNX3 in sorting and multivesicular body biogenesis.